Maresins: Specialized Proresolving Lipid Mediators and Their Potential Role in Inflammatory-Related Diseases - Shi Tang; Ming Wan; Wei Huang; R. C. Stanton; Yong Xu (Mediators of Inflammation, 2018)
Acute inflammatory responses are host-protective and normally self-limited; these responses can maintain cell homeostasis and promote defense against various infections and damage factors. However, when improperly managed or inappropriately activated, acute inflammation can lead to persistent and uncontrolled chronic inflammation, which is associated with many other chronic diseases including cardiovascular disease and metabolic disease. Recently, studies have shown that resolution of acute inflammation is a biosynthetically active process. Specialized proresolving lipid mediators (SPMs) known as resolvins and protectins are autacoids that resolve inflammation. A new family of anti-inflammatory and proresolving lipid mediators have recently been reported, known as maresins, which are biosynthesized from docosahexaenoic acid (DHA) by macrophages, have a conjugated double-bond system, and display strong anti-inflammatory and proresolving activity. Here, we review the biological actions, pathways, and mechanisms of maresins, which may play pivotal roles in the resolution of inflammation.